PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN CIREBON - Arum Anisa; Dharliana Hardjowikarto; Juwita Juwita (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The development of public sector organizations requires employees to perform optimally in providing services to the community. The Cirebon Regency Health Office, as a government agency engaged in health services, needs employees who possess competence, responsibility, and a high work ethic. This study aims to determine the influence of career development and work motivation on the performance of employees at the Cirebon Regency Health Office. This study employs a quantitative method with an associative approach. Data analysis techniques include validity tests, reliability tests, normality tests, multicollinearity tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination, utilizing IBM SPSS Statistics version 26 for Windows. The results indicate that, individually, in the t-test for variable X1, with a calculated t-value of 1.146 and a significance level of 0.254 (0.254 > 0.05) career development does not significantly affect employee performance, whereas for variable X2, with a t-value of 5.343 and a significance level of 0.000 (0.000 < 0.05) work motivation has a positive and significant effect on employee performance. Collectively, In the simultaneous analysis using the F-test, the calculated F-value was 23.812 with a significance level of 0.000 (below the 0.05) career development and work motivation significantly influence the performance of employees at the Cirebon Regency Health Office. Thus, work motivation is the more dominant factor in enhancing employee performance; however, career development must still be prioritized to ensure more optimal human resource management.